Climat social et professionnel : un comparatif écoles publiques / écoles privées - Lucile Boncompain-Katz (Recherches en Éducation)
In France, 13,4% of schools are catholic schools. In number of students, the pre-elementary and elementary catholic schools registered 892 115 children at the start of the school year on 2009, that represents 13,5% of students of primary age schooled by our country. Catholic schools’ teachers pass the Concours de Recrutement des Professeurs des Écoles but are also recruited and formed in a specific way. Are the values lent to the specificity of the catholic education translated by a school climate different from the state education? What are the differences between public and catholic education in terms of recruitment and initial training of the teachers and the headmasters? Can they change social relationships within a teaching staff and the expression of the « distributed leadership »? This article tries to answer these questions by leaning on official texts on one hand and by confronting them with the results of our inquiry led by questionnaires on the other hand.